Sacubitril/valsartan preserves kidney function in rats with cardiorenal syndrome after myocardial infarction - Kaja Knudsen Bergo; Einar Sjaastad Nordén; Bård Andre Bendiksen; Emil Knut Stenersen Espe; Gary McGinley; Ida Marie Hauge-Iversen; Rizwan Iqbal Hussain; Sabine Leh; Hans-Peter Marti; Lili Zhang; Ivar Sjaastad; Alessandro Cataliotti (PLoS ONE, 2025)
Renal dysfunction in heart failure increases mortality, limits treatment options and blunts responses to therapy. Angiotensin receptor-blocker and neprilysin inhibitors (ARNI) may preserve renal function by modulating both the renin-angiotensin-aldosterone system and the natriuretic peptide system. We investigated the renal effects of the ARNI Sacubitril/valsartan (Sac/Val) in rats with systolic dysfunction secondary to myocardial infarction. Male Sprague-Dawley rats underwent surgical MI induction and were randomized to six weeks of treatment with vehicle, valsartan or Sac/Val, and compared to sham operated animals. Renal function was evaluated by creatinine clearance, mean arterial pressure (MAP) by tail-cuff measurements, and cardiac function by magnetic resonance imaging and echocardiography. Vehicle treated animals developed cardiorenal syndrome, with impaired cardiac systolic function and mild renal dysfunction. Both valsartan and Sac/Val preserved renal function compared to vehicle (creatinine clearance mL/min [median with interquartile range]; sham 5.4 [4.8–6.0], vehicle 4.5 [4.1–5.1], valsartan 5.1 [5.1–5.5], Sac/Val 5.1 [5.0–5.6]; vehicle vs valsartan p = 0.034 and vehicle vs Sac/Val p = 0.044). MAP was reduced by both treatments compared to sham and vehicle groups (MAP mmHg ; sham 131 [116–138], vehicle 123 [115–132], valsartan 108 [99–112], Sac/Val 111 [99–119]; sham vs valsartan p < 0.001 and sham vs Sac/Val p = 0.003, vehicle vs valsartan p = 0.006 and vehicle vs Sac/Val p = 0.041). Only Sac/Val reduced left atrial dilatation (diameter mm ; sham 4.1 [3.7–4.4], vehicle 4.6 [3.8–5.6], valsartan 4.6 [4.1–5.5], Sac/Val 3.9 [3.6–4.5]; vehicle vs Sac/Val p = 0.047, valsartan vs Sac/Val p = 0.017) despite no improvement in systolic function in either treatment group. Sac/Val initiated in the acute post-MI phase preserved renal function to the same extent as valsartan alone and uniquely reduced left atrial dilatation, suggesting additional benefits beyond renoprotection in the setting of persistent systolic dysfunction.